Rat Density of Leptospirosis Case in Puskesmas Ngemplak Boyolali Regency - Muhamad Zulfikar Firdaus; Retno Hestiningsih; Martini Martini; M. Arie Wuryanto (Jurnal Kesehatan Masyarakat, 2019)
Leptospirosis is a disease caused by bacterial infection of Leptospira sp and a animals disease that can be transmitted to humans. Bacteria Leptospira live in the body of an infected animal and will come out with the animal's urine. Rats as a host acts as a reservoir plays an important role in the epidemiology of disease transmission and its close to human life that can be deadly, namely leptospirosis. This research is a descriptive study with a cross-sectional case study method. The variables of this study are the type of rat, sex of the rat, trap success, number of rats, density of Rats. Sampling by placing live-trap in a place that has sign traces of rats in 4 houses of leptospirosis patients and 14 houses around each house of leptospirosis patients. Sample size depends on the number of rats that are caught during this study. The results of the study showed that 14 male rats and 27 female rats were caught. Total number of rats caught was 41 rats with a success trap of 17.1% in dense category. Rats were caught from two types, namely Rattus tanezumi (rat's house) as many as 15 with an average weight of 202 gram and Rattus norvegicus (sewer rat) as many as 26 with an average weight of 239 gram.